Comparison of steady-state and transient thermal conductivity testing methods using different industrial rubber compounds. (December 2019) - Kerschbaumer, R.C.; Stieger, S.; Gschwandl, M.; Hutterer, T.; Fasching, M.; Lechner, B.; Meinhart, L.; Hildenbrandt, J.; Schrittesser, B.; Fuchs, P.F.; Berger, G.R.; Friesenbichler, W.
Abstract: Reliable material data, especially of the thermal conductivity as a function of temperature, are crucial for the virtual optimization of the rubber injection molding process. Due to the low thermal conductivity of rubber compounds, typically in the range from 0.15 to 0.4 W m −1 K −1, and the fact that the molding of the rubber part takes place in a heated mold via an energy-based crosslinking reaction, the total cycle time is in the range of minutes. Consequently, there is a vast potential for optimization of this lengthy production cycle. To determine the thermal conductivity of seven different rubber compounds, a stationary (Guarded Heat Flow Meter (GHF)), and three transient methods (Plane-Source (TPS), Line-Source (TLS), and Laser Flash Analysis (LFA)) were employed. Ancillary, the anisotropic TPS- and the LFA-method require the material parameters specific heat capacity as well as density. The TPS method also offers the possibility to perform an isotropic and an anisotropic measurement of the thermal conductivity. In general, filled rubber systems do not exhibit an isotropic material behavior. Due to filler orientation or diffusion of volatile substances to the surface, the values of the thermal conductivity obtained from TPS-method differ significantly from those of GHF or LFA. The TLS-measured thermal conductivity coincide with the GHF results; however, TLS is limited to rubber compounds containing no cross-linking system, and it is sensitive to emitted volatile substances. To conclude, both the GHF- and the LFA-method provide comparable results for all seven tested rubber compounds. Highlights: Thermal conductivity values are highly dependent on the measurement method. Some methods depend upon additional material parameters. Filler orientation has a crucial impact on thermal conductivity. Emission of volatile substances handicaps optical methods. Obtained values in plane- or thickness-direction differ up to a factor of two.